Fur functions as an activator of T6SS-mediated bacterial dominance and virulence in Aeromonas hydrophila - Li, Jihong; Wu, Zhihao; Hou, Yuting; Zhang, Yong-An; Zhou, Yang (Frontiers in Microbiology, 2023)
Aeromonas hydrophila, a ubiquitous bacterium in aquatic habitats with broad host ranges, has earned the nickname of a ‘Jack-of-all-trades’. However, there is still a limited understanding of the mechanism of how this bacterium fit the competition with other species in dynamic surroundings. The type VI secretion system (T6SS) is macromolecular machinery found in Gram-negative bacteria’s cell envelope that is responsible for bacterial killing and/or pathogenicity towards different host cells. In this study, the depression of A. hydrophila T6SS under iron-limiting conditions was detected. The ferric uptake regulator (Fur) was then found to act as an activator of T6SS by directly binding to the Fur box region in vipA promoter in the T6SS gene cluster. The transcription of vipA was repressed in Δfur. Moreover, the inactivation of Fur resulted in inconsiderable defects in the interbacterial competition activity and pathogenicity of A. hydrophila in vitro and in vivo. These findings provide the first direct evidence that Fur positively regulates the expression and functional activity of T6SS in Gram-negative bacteria and will help to understand the fascinating mechanism of competitive advantage for A. hydrophila in different ecological niches.